Significado paleoambiental de registro palinológico da ESEC Mata Preta, planalto subtropical com araucárias, Abelardo Luz (SC) - Moraes, Isis Fumagalli de (2024)
This work presents the results of a palynological analysis conducted at ESEC da Mata Preta, in the Subtropical Plateau with Araucárias, Abelardo Luz (SC), Brazil. The objective of this study was to investigate the paleoenvironmental response to Quaternary environmental changes in the Subtropical Araucária Plateau. For this, a 320 cm deep sedimentary core was collected in a peat bog area within ESEC-MP. Samples were separated for radiocarbon dating, and 81 samples were treated and processed according to standard Quaternary Palynology chemical processing. The samples were read every 8 cm, and for each sample 300 grains of terrestrial pollen were counted, the spores were counted separately. A palynological diagram was generated using Tília software, version 2.6.1, and cluster analysis was used to determine environmental phases. The basal age of the core was ~39,647 years BP, Late Pleistocene. The cluster analysis divided the testimony into three environmental phases and two subphases, namely: AL Ia, AL-Ib; AL-II; AL-III. The Late Pleistocene is characterized by a cold and humid climate. Forest regeneration after the Last Glacial Maximum (18,000 to 20,000 years BP) was identified. The field-forest mosaic characterizes the vegetation. The peat bog has been present in this area for at least ~40,000 years. The results found in this research corroborate with other works already conducted in the Subtropical Plateau with Araucárias.